CONFORTO TÉRMICO EM EDIFICAÇÕES DE CLIMAS TROPICAIS SECOS ENSINO NA REGIÃO CENTRO-SUL DO BRASIL - Pollyanna Meireles Cordeiro (2023)
This research aimed to investigate the perception, sensations, and thermal and air velocity preferences of university students in buildings located in dry tropical climates during the winter and autumn seasons in the cities of Campo Grande and Naviraí in Mato Grosso do Sul, Central-West region of Brazil. Measurements of microclimatic internal physical parameters (air temperature, mean radiant temperature, air velocity, and relative humidity) were conducted, along with the collection of external data (relative humidity and air temperature). Simultaneously, information about the spaces provided by the users during classes was collected through electronic questionnaires. A total of 1,587 thermal comfort and air velocity assessment votes were obtained, which were tabulated and processed using descriptive statistics. The comfort temperature for Campo Grande was 23.4 °C, and for Naviraí, it was 22.4 °C. The thermal discomfort found in the sample was 16.8%, with 9.3% in artificially conditioned environments and 22.5% in environments without air conditioning equipment. Despite the reported high thermal discomfort, the thermal unacceptability was only 4.6%. A mean air velocity of 0.14m/s was reported as sufficient. Predicted Percentage of Dissatisfied (PPD) and Predicted Mean Vote (PMV) did not accurately estimate the users' sensations. This research investigated the use of air conditioning systems and fans in the analyzed region. The findings contribute to the understanding and provide insights into issues related to human thermal comfort in Brazil.